Good days, bad days: Do sacrifices improve relationship quality?. (November 2013) - Totenhagen, Casey J.; Curran, Melissa A.; Serido, Joyce; Butler, Emily A.
We utilized interdependence theory and conservation of resources to understand how relational sacrifices and hassles impact positive relationship quality constructs (i.e., satisfaction, closeness, and commitment) in romantic relationships ( N = 164 couples; 328 individuals). Using daily diary data to examine actor and partner effects, we found that individuals' sacrifices were positively linked with their own commitment but not with satisfaction or closeness. We also found that hassles were negatively linked with one's own and one's partner's satisfaction and closeness but not with commitment. When examined together, sacrifices remained beneficial for one's own commitment but only when increased sacrifices occurred on days with low hassles. We discuss the unique pathways of sacrifices and hassles, both on their own and considered together.